Tenure Profiles and Efficient Separation in a Stochastic Productivity Model - Sebastian Buhai; Coen N. Teulings (Tinbergen Institute, 2005)
This paper provides a new way of analyzing tenure profiles in wages, by modelling simultaneously the evolution of wages and the distribution of tenures. Starting point is the observation that within-job log wages for an individual can be described by random walk. We develop a theoretical model based on efficient bargaining, where both log outside wage and log wage in the current job follow a random walk. This setting allows the application of real option theory. We derive the efficient separation rule, which stipulates that workers switch jobs when the difference between the outside wage and the wage in the current job reaches a threshold. The model fits well the observed distribution of job tenures. Since we observe outside wages only at job start and job separation, our empirical analysis of with job wage growth is based on expected wage growth conditional on the outside wages at both dates. Our modelling allows testing of the efficient bargaining hypothesis. The model is estimated on the PSID.
Keywords: C51; C52; J63; 330; random productivity growth; efficient bargaining; job tenure; wage growth; wage-tenure profiles; option theory; Betriebszugehörigkeit; Lohn; Erwerbsverlauf; Verhandlungstheorie; Realoptionsansatz